A literature review on career chance experiences: Conceptualization and sociocultural influences on research. Issue 3 (1st April 2022) - Kim, Namhee
Abstract: The purpose of this study is to review the literature on career chance to show how it has developed and been conceptualized and to identify what sociocultural factors have been associated with career change research. Thirty‐eight scholarly empirical journal articles were collected based on the search criteria and reviewed using Torraco's integrative literature review and Garrard's matrix method. The results show that career chance experiences have been conceptualized based on attributes such as inability to plan, human actions involved, and changes in direction, but the current research does not adequately account for cultural traditions.